Phylogenetic Analysis of Human Papillomavirus 16 and 52 L1 Gene from Cervical Cancer in Bandung, Indonesia - Mutia Latief; Ika Agus Rini; Gita Widya Pradini; Gatot Nyarumenteng Adhipurnawan Winarno; Edhyana Sahiratmadja; Herman Susanto (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Chronic infection with high-risk type of human papillomavirus (HPV) can cause cervical cancer. Previous studies showed that multiple infections of HPV are found in cervical cancer caused by multiple HPV infections and the most common are HPV-16 and HPV-52. The origin of HPV-16 circulating in Indonesia varies. The purpose of this study was to explore the origin of multiple infections of HPV-52 and HPV-16 in cervical cancer by using a phylogenetic tree.METHODS: During July-November 2010, 100 women were diagnosed with cervical cancer in the Department of Obstetrics and Gynecology, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Only 96 patients were involved in this study. Ninety-six samples of HPV deoxyribonucleic acid (DNA) were isolated from biopsied tissue of cervical cancer. Multiple infections of HPV genotypes HPV-16 and HPV-52 were confirmed by using the linear assay for HPV genotyping test. Afterward,HPV-52L1 gene was amplified by using self-designed primer. L1 gene was also sequenced and analyzed using phylogenetic program (MEGA6.06).RESULTS: The result of phylogenetic tree construction showed that isolated HPV-52 originated from multiple infections of HPV-16 and HPV-52 from cervical cancer patients in Bandung were in a subgroup with isolates originating from EU077219 Canada (America) and KT799980 southwest China (Asia). Isolate HPV-16 in one subgroup with isolates originating from KU951191.1 (Southwest China).CONCLUSION: L1 gene sequence from multiple infections isolated from HPV-16 and HPV-52 from cervical cancer patients in Bandung refers to the variation of L1 gene reported from Canada and southwest China. This proves that Indonesia’s HPV clusters are located in the strains found in America and Asia.KEYWORDS: multiple infections, HPV-16, HPV-52, L1 gene, phylogenetic